Microscopic investigation of the influence of complex stress states on internal erosion and its impacts on critical hydraulic gradients. (17th October 2022) - Zhou, Chuang; Qian, Jian‐Gu; Yin, Zhen‐Yu
Abstract: Internal erosion involves the loss of fine particles within the matrix of coarse particles under seepage flow, posing a severe threat to hydraulic structures. This paper focuses on internal erosion considering anisotropic stress conditions. The influence of the anisotropic stress state, represented by vertical stress equal to, bigger than, or smaller than horizontal stress, was investigated using coupled computational fluid dynamics (CFD) and the discrete element method (DEM). Results show that the loss of fine particle specimens under anisotropic stress conditions is greater than that for samples under isotropic stress states, as the loss of fine particles leads to an evolution of anisotropy into isotropy, with local contact force chains gradually forming spatially isotropic structures. The strong force chains of specimens under triaxial compression were also found to develop a dominant orientation in the vertical direction, leading to clogging in the upward migration of fine particles and increasing the critical hydraulic gradient. In addition, the evolution of void ratio, hydraulic drag force, connectivity, and coordination number has also been analyzed to exhibit the influence of stress anisotropy on internal erosion.